RECOMMENDATIONS FOR SUSTAINABLE MANAGEMENT OF WOOD RESOURCES IN KRĀSLAVAS DISTRICT - Valters, Arvis; Lazdāns, Dainis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Research work is made in Krāslavas district. The purpose of this work was to carry out Krāslavas district wood resources stock to research and develop recommendations for the sustainable management wood resources in Krāslavas district.: There is newer made those kind of research works for wood stock in Krāslavas district importance of this research work is provided by forestry sector who is one of most important sectors in Krāslavas district This sector provide important Krāslava forestry is one of the leading industries that perform important ecological, economic and social functions, the EU in April 2015 adopted a new EU forestry strategy (COM (2013) 0659), which has offered new guidelines for policy-making in the European sectors closely related to forests. This strategy sets out the main principles of sustainable forest wood management. Krāslavas district needs to take stock wood resources to research and develop recommendations for the sustainable management of wood resources in district.